ANALISIS KEABSAHAN TRANSAKSI JUAL BELI ONLINE YANG DILAKUKAN ANAK DIBAWAH UMUR MENURUT HUKUM ISLAM DAN HUKUM PERDATA INDONESIA - Sinta Bela; KHUMEDI JA'FAR; MAIMUN; MUHAMMAD ZAKI; LIKY FAISAL (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2022)
Buying and selling online according to Islamic law is allowed as long as online buying and selling transactions do not contain fraud, coercion and persecution. In Islam, it must be carried out in accordance with the provisions of the Shari'a, which must meet the pillars and conditions of buying and selling. The three pillars of buying and selling must exist, namely igat, contract, 'aqīd (seller and buyer) with mumayyiz and sound mind conditions so that the sale and purchase is valid. The legitimacy of buying and selling online by minors has been regulated in Article 1320 of the Civil Code. The problem that will be discussed in this thesis is the analysis of the validity of online buying and selling transactions carried out by minors according to Islamic law and Indonesian civil law. This research is a library research (Library research). After the data was collected, the researchers conducted an analysis using a comparative descriptive method of qualitative analysis with a thinking approach using a deductive method. The results of the study show that Article 1320 of the Civil Code can still be said to be valid, but the legal force is weak because it does not meet the legal requirements of the agreement. Meanwhile, according to Islamic law, it is permissible based on the pillars and conditions of online buying and selling provided that the child is mumayyiz and the sale and purchase item is of low value and must have permission from his guardian.